anonymous
  • anonymous
\[a_{n+2}-(2^{n+1}+2^{-n}) a_{n+1}+a_n=0\]\(a_1=1, a_2=3\). Find \(a_n\).
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
What have you tried?
ganeshie8
  • ganeshie8
I saw this problem before and know a solution which is somewhat complicated. I'm going to wait for other solutions :) I think this problem is composed by mukushla, he wants us to try...
anonymous
  • anonymous
thanks gane :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

Empty
  • Empty
Here's my thoughts so far: The ordinary power series generating function satisfies this equation: \[f(x)-\frac{2}{x} f(\frac{x}{2})-2f(2x)-\frac{1}{x}=0\]
anonymous
  • anonymous
@Empty you study physics? That seems like a physicist approach!
Empty
  • Empty
I study everything I can get my hands on lol
anonymous
  • anonymous
good :) btw, how you got that?
Empty
  • Empty
Sorry that wasn't quite the link I wanted, this is the book I'm reading currently generatingfunctionology: https://www.math.upenn.edu/~wilf/DownldGF.html
anonymous
  • anonymous
thanks for the link
anonymous
  • anonymous
\[\begin{split} a_n &= \left(2^{n+1}+2^{-n}\right)a_{n-1}-a_{n-2} =ba_{n-1}-a_{n-2}\\ &= b\left(ba_{n-2}-a_{n-3}\right)-a_{n-2} \\ &= \left(b^2-1\right)a_{n-2}-a_{n-3} \\ &= \left(b^3-b-1\right)a_{n-3}-a_{n-4} \\ &= \left(b^{k+1}-\sum_{m=0}^{k-1}b^m\right)a_{n-k-1}-a_{n-k-2} \\ &= \left(b^{k+1}-\sum_{m=0}^{k-1}b^m\right)a_{n-k-1}-a_{n-k-2} \\ &= \left(b^{k+1}-\frac{1-b^{k}}{1-b}\right)a_{n-k-1}-a_{n-k-2} \\ \end{split}\]For our base case, we plug in \(k=n-3\): \[ a_n = \left(b^{n-2}-\frac{1-b^{n-3}}{1-b}\right)a_2+a_1 = 3\left(b^{n-2}-\frac{1-b^{n-3}}{1-b}\right)+1 \]Then substitute the \(b=2^{n+1}+2^{-n}\).
anonymous
  • anonymous
It looks good, maybe you have some little mistakes, find \(a_3\) from your formula and once again directly from the relation and compare, see if the formula is right or not :)
anonymous
  • anonymous
\[\begin{split} a_n &= \left(2^{n+1}+2^{-n}\right)a_{n-1}-a_{n-2} =ba_{n-1}-a_{n-2}\\ &= b\left(ba_{n-2}-a_{n-3}\right)-a_{n-2} \\ &= \left(b^2-1\right)a_{n-2}-a_{n-3} \\ &= \left(b^3-b-1\right)a_{n-3}-a_{n-4} \\ &= \left(b^{k}-\sum_{m=0}^{k-2}b^m\right)a_{n-k}-a_{n-k-1} \\ &= \left(b^{k}-\sum_{m=0}^{k-2}b^m\right)a_{n-k}-a_{n-k-1} \\ &= \left(b^{k}-\frac{1-b^{k-1}}{1-b}\right)a_{n-k}-a_{n-k-1} \\ \end{split}\]For our base case, we plug in \(k=n-2\): \[ a_n = \left(b^{n-2}-\frac{1-b^{n-3}}{1-b}\right)a_2+a_1 = 3\left(b^{n-2}-\frac{1-b^{n-3}}{1-b}\right)+1 \]Then substitute the \(b=2^{n+1}+2^{-n}\).
anonymous
  • anonymous
There is a special case at \(n=3\) because for that case, we have the coefficient \(b\) rather than \(b-\frac{1}{1-b}\)
anonymous
  • anonymous
In fact, all the \(n<4\) cases probably will not hold, because that geometric sum assumes higher values for \(n\).
anonymous
  • anonymous
thanks

Looking for something else?

Not the answer you are looking for? Search for more explanations.